Fish oil supplementation in obese rats ameliorates metabolic syndrome response - D.M.B. Freitas; B.A.C. Oliveira; L.D.V. Henschel; M.H.A.P.C. Oliveira; M. Zazula; E. Horlem; D.F.S. Rodriguez; S.R.S. Carvalhal; F. Iagher; R. Fernandez; K. Naliwaiko; L.C. Fernandes (Brazilian Journal of Medical and Biological Research, 2024)
Accumulation of visceral adipose tissue is associated with metabolic syndrome (MS), insulin resistance, and dyslipidemia. Here we examined several morphometric and biochemical parameters linked to MS in a rodent litter size reduction model, and how a 30-day fish oil (FO) supplementation affected these parameters. On day 3 post-birth, pups were divided into groups of ten or three. On day 22, rats were split into control (C) and small litter (SL) until 60 days old. Then, after metabolic disturbance and obesity were confirmed, FO supplementation started for 30 days and the new groups were named control (C), FO supplemented (FO), obese (Ob), and obese FO supplemented (ObFO). Comparison was performed by Student t-test or 2-way ANOVA followed by Tukey post hoc test. At the end of the 60-day period, SL rats were hyperphagic, obese, hypoinsulinemic, normoglycemic, and had high visceral fat depot and high interleukin (IL)-6 plasma concentration. Obese rats at 90 days of age were fatter, hyperphagic, hyperglycemic, hypertriacylgliceromic, hipoinsulinemic, with low innate immune response. IL-6 production ex vivo was higher, but in plasma it was not different from the control group. FO supplementation brought all biochemical changes to normal values, normalized food intake, and reduced body weight and fat mass in obese rats. The innate immune response was improved but still not as efficient as in lean animals. Our results suggested that as soon MS appears, FO supplementation must be used to ameliorate the morpho- and biochemical effects caused by MS and improve the innate immune response.